PEMANFAATAN NIPAH (Nypa frutican Wurmb) DI DUSUN SUKA MAJU DESA SUNGAI SEPETI KECAMATAN SEPONTI KABUPATEN KAYONG UTARA - Suparto, .; Oramahi, H A; Sisillia, Lolyta (JURNAL HUTAN LESTARI, 2019)
Nipah is one of the non-timber forest products whose all the part of the plant can be utilized. This research aimed to find out the information on various forms of utilization of nipah by the community of Suka Maju hamlet in Sungai Sepeti village Kayong Utara regency. This study used a descriptive method with direct interview technique to a number of respondents to get response. Sampling was perfomed with snowball sampling method. The results showed that the community of Suka Maju Hamlet of Sungai Sepeti village in Seponti Subdistrict of Kayong Utara Regency utilized 5 parts of the nipah namely leaves, shoots, sticks, fruit, and flowers. Using The parts of the nipah, people can use its leaves as roof or as raw building material, Â nipah shoots for making of art craft woven mats, rice countainer, and cigarette, sticks on the sticks for making brooms, the fruit for making kolang kaling, an the flower can be consumed and used as a temporary treatment for fever.Keywords: Nipah, Snowball Sampling, Suka Maju Hamlet, Utilization